7 + 2lnx = 6

2 Answers | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

7 + 2 ln x = 6

Move 7 to the right side by subtracting 7 from both sides:

==> 2 ln x = 6-7

==> 2 ln x = -1

Now we know that 2 ln x = ln x^2

==> ln x^2 = -1

==> x^2 = e^-1

==> x^2 = 1/e

==>x = 1/sqrt(e)

kjcdb8er's profile pic

kjcdb8er | Teacher | (Level 1) Associate Educator

Posted on

7 + 2 ln(x) = 6

2 ln(x) = 6 - 7 = -1

ln(x) = -1/2

e^(ln x) = e^-1/2

x = 1/sqrt(e)

We’ve answered 318,982 questions. We can answer yours, too.

Ask a question